Coping flexibility predicts post-traumatic stress disorder and depression in human rights advocates. Issue 4 (2nd October 2017) - Rodin, Rebecca; Bonanno, George A.; Knuckey, Sarah; Satterthwaite, Margaret L.; Hart, Roland; Joscelyne, Amy; Bryant, Richard A.; Brown, Adam D.
ABSTRACT: An emerging body of research on individuals exposed to trauma shows that the ability to flexibly employ different coping styles is associated with better adjustment. Specifically, individuals who use both "trauma-focused" (focusing on the experience and significance of a potentially traumatic event) and "forward-focused" (optimism, helping others, goal-oriented thinking) coping styles exhibit less psychological disturbance after trauma exposure than those with less coping flexibility. We investigated whether greater coping flexibility is associated with less Post-traumatic Stress Disorder (PTSD) and Major Depressive Disorder (MDD) in an international sample of human rights advocates. In an online, cross-sectional study, 346 international human rights advocates completed self-reported measures of PTSD, MDD, trauma exposure, and the Perceived Ability to Cope with Trauma (PACT) scale. Results showed that coping flexibility was associated with lower rates and symptom severity of PTSD and MDD. Whereas both trauma-focused and forward-focused coping were associated with lower rates of PTSD, the inverse relationship between coping flexibility and MDD was driven primarily by less forward-focused coping. These findings are the first to show that lower levels of coping flexibility may be an important factor underlying vulnerability to PTSD and MDD among human rights advocates. Longitudinal studies are needed to clarify whether coping flexibility can mitigate the potential negative mental health impact of traumatic stress over the course of one's career in international human rights advocacy.